Brain training with the body in mind: Towards gamified approach-avoidance training using virtual reality. Issue 151 (July 2021) - Kakoschke, Naomi; Page, Rowan; de Courten, Barbora; Verdejo-Garcia, Antonio; McCormack, Jon
Highlights: Approach-avoidance training is a novel intervention for modifying cognitive biases. We co-created a gamified virtual reality (VR) interface to deliver the training. We compared the VR interface with other interfaces (smartphone app; computer). The VR version received higher engagement, flow, immersion ratings than other interfaces. Immersive environments may be a more engaging way to deliver cognitive training. Abstract: Approach-Avoidance Training (AAT) is a promising intervention for modifying automatic cognitive biases towards highly palatable, but unhealthy food cues. As AAT requires repetitive motor exercises in response to basic visual stimuli, users typically find the training unengaging. Virtual reality (VR) provides an innovative opportunity for delivering more engaging, and ultimately, effective training through presenting virtual sensory stimuli in the virtual environment that replace the user's sensory stimuli. In this study, we compared user experience (flow, immersion, engagement) and performance (accuracy, approach bias) of AAT delivered via three interfaces (computer, smartphone, and VR). Participants were 24 adults (50% female; n = 12) aged 20–45 years old ( M = 31.05, SD = 8.18). Results showed that VR-delivered AAT received higher engagement, flow, and immersion ratings from users than AAT delivered via a computer or smartphone application. Participants also made fewer errors on the VR delivered AAT. Thus, in our experiment, VR was a more engaging and effective way to deliver the training. Future research should examine the potential of VR to further leverage gamification elements within more immersive environments.